1998
DOI: 10.1002/(sici)1097-0142(19980815)83:4<706::aid-cncr11>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer care in older women

Abstract: BACKGROUND The authors studied older women with breast cancer and asked: 1) where do older women get information regarding breast cancer care and how helpful do they perceive each of these sources to be? and 2) what aspects of social support are associated with older women's general and breast cancer specific emotional health outcomes? METHODS To be eligible, women had to be at least 55 years of age and newly diagnosed with TNM Stage I or II breast cancer. Data were collected from women's surgical records and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Firstly, it is speculated that elderly cancer patients often prefer to obtain their information directly from their clinician [18,19] and would therefore tend to seek out secondary sources of information, such as self-help groups, less often. They may also be less willing and accustomed to exploring information pertaining to cancer treatments and management thereof which may be outside the regimen suggested by the physician [19,20]. In addition, some of the supportive services offered may not be perceived by elderly cancer patients as relevant for them such as body image issues and embarking on a physical activity and fitness program.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it is speculated that elderly cancer patients often prefer to obtain their information directly from their clinician [18,19] and would therefore tend to seek out secondary sources of information, such as self-help groups, less often. They may also be less willing and accustomed to exploring information pertaining to cancer treatments and management thereof which may be outside the regimen suggested by the physician [19,20]. In addition, some of the supportive services offered may not be perceived by elderly cancer patients as relevant for them such as body image issues and embarking on a physical activity and fitness program.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this difference is that the elderly have a greater likelihood of experiencing comorbid medical conditions, which are associated with poor health and diminished quality of life in cancer survivors [50]. Studies have also found that elderly breast cancer survivors are more likely than younger women to report less participatory decision making, fewer supportive interactions, less time spent with physicians as well as lower levels of perceived social support and diminishing size of support networks [51, 52]. These factors also influence symptom experience and management.…”
Section: Discussionmentioning
confidence: 99%
“…Internal consistency coefficients were ≥ .83 for Latinas and Whites. Breast cancer-specific emotional health was assessed with four items, including worrying about the breast cancer recurring or worrying about the family's ability to manage if the participant gets sicker (Silliman, Dukes, Sullivan, & Kaplan, 1998). The scale demonstrates convergent validity with important quality of life outcomes (Maly et al, 2008).…”
Section: Methodsmentioning
confidence: 99%